De l'émotion dans la conversion. Interactions émotionnelles et apprentissage au sein du bouddhisme dzogchen occidentalisé - Bianchi, Maria Alessandra (Social compass, 2018)
This article presents an analysis of the role of emotions during the conversion process to a specific Tibetan Buddhism teaching - the dzogchen. It is based on qualitative data gathered from field research in France and in Italy amongst two organisations. I draw on Arlie Russel Hochschild's interactionist approach to demonstrate that the aspiring convert carries out an emotional work on him/herself as a means of learning certain feeling rules proposed by the dzogchen organisations. This dynamic contributes significantly in the conversion process, which takes place during intersubjective interactions. Firstly, the conversion agents' use tools such as training devices', symbols, and a system that helps decide between the emotions to show and to avoid. This system stimulates the collective learning process of the dzogchen feeling rules by the social actor. Secondly, the dzogchen practitioners, by interacting with each other, learn to adjust their emotional behaviour.